CBD enhances the cognitive score of adolescent rats prenatally exposed to THC and fine-tunes relevant effectors of hippocampal plasticity - Castelli, Valentina; Lavanco, Gianluca; D’Amico, Cesare; Feo, Salvatore; Tringali, Giuseppe; Kuchar, Martin; Cannizzaro, Carla; Brancato, Anna (Frontiers in Pharmacology, 2023)
An altered neurodevelopmental trajectory associated with prenatal exposure to ∆-9tetrahydrocannabinol (THC) leads to aberrant cognitive processing through a perturbation in the effectors of hippocampal plasticity in the juvenile offspring. As adolescence presents a unique window of opportunity for 'brain reprogramming', we aimed at assessing the role of the nonpsychoactive phytocannabinoid cannabidiol (CBD) as a rescue strategy to temper prenatal THCinduced harm. To this aim, Wistar rats prenatally exposed to THC (2 mg/kg s.c.) or vehicle (gestational days 5-20) were tested for specific indexes of spatial and configural memory in the reinforcement-motivated Can test and in the aversion-driven Barnes maze test during adolescence. Markers of hippocampal excitatory plasticity and endocannabinoid signaling -NMDAR subunits NR1 and 2A-, mGluR5-, and their respective scaffold proteins PSD95-and Homer 1-; CB1R-and the neuromodulatory protein HINT1 mRNA levels were evaluated. CBD (40 mg/kg i.p.) was administered to the adolescent offspring before the cognitive tasks. The present results show that prenatal THC impairs hippocampal memory functions and the underlying synaptic plasticity; CBD is able to mitigate cognitive impairment in both reinforcement-and aversion-related tasks and the neuroadaptation of hippocampal excitatory synapses and CB1R-related signaling. While this research shows CBD potential in dampening prenatal THC-induced consequences, we point out the urgency to curb cannabis use during pregnancy in order to avoid detrimental bio-behavioral outcomes in the offspring.